Estudo comparativo entre sistemas de limpeza de gases de alto-forno em siderúrgicas não-integradas a carvão vegetal e alternativa de reaproveitamento do pó do balão - Eduardo Delano Leite Ribeiro (2011)
The non-integrated steel industry charcoal has predominance in Minas Gerais, concentrating 106 blast furnaces with a production capacity of approximately 5.500.000t.ano-1. In 2001, was enacted by COPAM - the Regulatory Determination nº49/2011 allowed the environmental regulation of the sector and established mechanisms of control. Aftereight years in the force were held two master's theses by experts from the environmental agency to updating data, to propose environmental performance indicators, and research on energy use of blast furnace gas.Emphasis was given to the subject of atmospheric notably the cleaning system of blast furnace gas. According to data collected in these studies, the system of gas cleaning done wet, with implementation of scrubbers, showed the same efficiency of dry cleaning, via inertial collectors and cyclones according to results presented in selfmonitoring program sent the environmental agency for the sector units. In the face of inconsistency of data from such monitoring, then a study was proposed by isokinetic sampling aiming to determine the concentration of particulate matter emitted by seven blast furnaces of steel Metalsider Ltda.. Samples were taken at the blast furnaces operating with the system dry, dust collectors and, later, its replacement with gas scrubbers. The cleaning system changes were made gradually as the oven reaches its final campaign. The results show that the wet system, adopting scrubbers, Venturi hadhigher removal efficiency of particulates indicating that the most appropriate equipment to clean the gas in blast furnaces, mainly targeting the gas energy. The alternative of using the powder collected in the primary dust collector, the gas cleaning system was studied to evaluate the rate of addition of 3% of the residue on clay for making bricks. The result indicated that the addition of powder flask in this ratiodoes not change the classification of clay blanketing guaranteeing of any heavy metals present in the residue. These results is strongly suggested the creation of a specific Regulatory Determination on the possibility of reuse of this material since this percentage of recovery, the waste has not changed its classification according to ABNT NBR 10.004.